In-orbit results of Delfi-n3Xt: Lessons learned and move forward. (April 2016) - Guo, Jian; Bouwmeester, Jasper; Gill, Eberhard
Abstract: This paper provides an update of the Delfi nanosatellite programme of the Delft University of Technology (TU Delft), with a focus on the recent in-orbit results of the second TU Delft satellite Delfi-n3Xt. In addition to the educational objective that has been reached with more than 80 students involved in the project, most of the technological objectives of Delfi-n3Xt have also been fulfilled with successful in-orbit demonstrations of payloads and platform. Among these demonstrations, four are highlighted in this paper, including a solid cool gas micropropulsion system, a new type of solar cell, a more robust Command and Data Handling Subsystem (CDHS), and a highly integrated Attitude Determination and Control Subsystem (ADCS) that performs three-axis active control using reaction wheels. Through the development of Delfi-n3Xt, significant experiences and lessons have been learned, which motivated a further step towards DelFFi, the third Delfi CubeSat mission, to demonstrate autonomous formation flying using two CubeSats named Delta and Phi. A brief update of the DelFFi mission is also provided. Abstract : Highlights: In-orbit results of the second TU Delft satellite Delfi-n3Xt are presented. A solid cool gas micropropulsion system is demonstrated in orbit. In-orbit results of a robust CDHS and a highly integrated ADCS are provided. Lessons learned and development status of new satellites are reported.